1999
DOI: 10.1161/01.atv.19.1.178
|View full text |Cite
|
Sign up to set email alerts
|

The Proliferative Effect of Vascular Endothelial Growth Factor Requires Protein Kinase C-α and Protein Kinase C-ζ

Abstract: Abstract-The heparin-binding protein vascular endothelial growth factor (VEGF) is a highly specific growth factor for endothelial cells. VEGF binds to specific tyrosine kinase receptors, which mediate intracellular signaling. We investigated 2 hypotheses: (1) VEGF affects intracellular calcium [Ca 2ϩ ] i regulation and [Ca 2ϩ ] i -dependent messenger systems; and (2) these mechanisms are important for VEGF's proliferative effects. [Ca 2ϩ ] i was measured in human umbilical vein endothelial cells using fura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 48 publications
3
44
2
Order By: Relevance
“…In contrast with observations made in BAEC, Wellner et al (52) associated activation of PKC-␣ and PKC-with the proliferative response induced by VEGF in HUVEC. We were unable to detect expression of PKC␤ in HUVEC and found that by acting through KDR, VEGF induced membrane translocation of PKC-⑀ but not PKC-␣ or PKC-.…”
Section: Discussioncontrasting
confidence: 56%
“…In contrast with observations made in BAEC, Wellner et al (52) associated activation of PKC-␣ and PKC-with the proliferative response induced by VEGF in HUVEC. We were unable to detect expression of PKC␤ in HUVEC and found that by acting through KDR, VEGF induced membrane translocation of PKC-⑀ but not PKC-␣ or PKC-.…”
Section: Discussioncontrasting
confidence: 56%
“…Indeed VEGF-A stimulates PLC-g-mediated hydrolysis of PI(4,5)P 2 to generate DG, which then leads to activation of PKC (Matsumoto and Claesson-Welsh, 2001). PKC-a and -b isoforms are required for VEGF-stimulated cell proliferation and migration in vitro, as well as for neovascularization in vivo (Wellner et al, 1999;Wang et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, in endothelial cells, the increased activity of PKCa, which indeed is activated by VEGF-A in a DG-mediated manner, is expected to enhance rather than inhibit VEGF-A-induced angiogenic response (Wellner et al, 1999;Matsumoto and Claesson-Welsh, 2001;Wang et al, 2002). Conversely, the role of activation of Dgk-a in VEGF-A angiogenic signaling may consist in the generation of PA-mediated signals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimulation with PMA alone resulted in a striking increase in TF expression, indicating that PKC plays a central role in VEGF/TNF-induced up-regulation of TF. Previously, several isoforms of PKC such as PKC-␣, -␤, -␥, -, and -⑀ have been shown to be activated by VEGF stimulation (34,(37)(38). Because TNF has also been shown to activate PKC (39), the synergistic up-regulation of TF induced by VEGF and TNF may occur at the level of PKC.…”
Section: Discussionmentioning
confidence: 99%